THE ROLE OF THE ENVIRONMENTAL ECONOMY IN THE COUNTRY'S ECONOMY - Egamberdiev Shavkatbek Shakhobiddin ugli; Safarov Asadbek Jasurbek ugli; Nuriddinov Abdulaziz Rohatbek ugli; Abdumalikov Dilmuhammad Dilyorbek ugli (Scholar Express Journals, 2024)
This article covers the area of Environmental Economics and its ecology with dependence, some modern problems of the Environmental economy and their there have been reflections on the problems affecting,the relationship of the Environmental economy to the economy of the country.
Keywords: Environment; economy; climate; pollution